Comparative analysis of adrenergic reactivity of erythrocytes in patients with myocardial infarction depending on the severity of coronary obstruction - D. A. Vorobyova; T. Yu. Rebrova; S. A. Afanasyev; V. V. Ryabov (Российский кардиологический журнал)
Aim. To study the parameters of beta-adrenergic reactivity of membrane (p-ARM) of erythrocytes in patients with myocardial infarction with nonobstructive coronary arteries (MINOCA) and single-vessel CAD.Material and methods. The study included 40 patients with MI (experimental group — 19 patients; control group — 21 patients). Three patients (15,7%) with diagnosed acute myocarditis were excluded from the analysis. Levels of β -ARM were determined upon admission, on the 2nd, 4th and 7th day after MI. The normal range of β -ARM were <20 CU.Results. In a significant proportion of patients, p-ARM values were two times higher than normal values. The median β -ARM in the experimental group at admission was 41,7 (29,0;61,5) CU, on the day 1 — 48,6 (38,5;57,3) CU, day 4 — 49,4 (39,0;63,3) CU, day 7 — 53,5 (35,2;67,7) CU. In the control group, the median p-ARM at admission was 52,5 (25,4;64,5) CU, day 1 — 51,6 (28,3;56,9) CU, day 4 — 48,5 (34,9;61,2) CU, day 7 — 45,1 (32,2;68,9) CU. Static analysis of p-ARM at all followup periods did not show differences between the groups by median level (p>0,05). The curves of β -ARM median changes show its multidirectional dynamics in the studied groups. During the hospitalization, in the group of patients with MINOCA there was a downward trend in β -ARM. In the control group, there was a tendency to increase of β -ARM. A statistically significant correlation of β -ARM with the ejection fraction (r=0,83, p=0,0007) and a moderate correlation between the p-ARM level on the 4th day and GRACE risk (r=0,55, p=0,03) in patients of the control group were revealed.Conclusion. β-ARM values in patients with MINOCA were doubled, and this increase was comparable to levels in patients with obstructive CAD. During the hospitalization, the β -ARM levels did not significantly change, despite the use of beta-blockers.